2019
DOI: 10.35940/ijitee.j9684.0881019
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis on Social Media Big Data With Multiple Tweet Words

Abstract: The main objective of this paper is Analyze the reviews of Social Media Big Data of E-Commerce product's. And provides helpful result to online shopping customers about the product quality and also provides helpful decision making idea to the business about the customer's mostly liking and buying products. This covers all features or opinion words, like capitalized words, sequence of repeated letters, emoji, slang words, exclamatory words, intensifiers, modifiers, conjunction words and negation words etc avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…In the present research, different supervised machine learning has been developed, resulting in a comparative analysis for the selection of the most accurate and effective algorithm for the built dataset. In the study, the predicted sentiment polarity for a given tweet is either classified as positive or negative, as developed by Maheswari and Dhenakaran (2019). For the feature vector formation required as an input for these machine learning classification algorithms, the training dataset is transformed into a bag of words where each entry corresponds to the number of occurrences of a particular term in the sentence (Soumya and Pramod, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In the present research, different supervised machine learning has been developed, resulting in a comparative analysis for the selection of the most accurate and effective algorithm for the built dataset. In the study, the predicted sentiment polarity for a given tweet is either classified as positive or negative, as developed by Maheswari and Dhenakaran (2019). For the feature vector formation required as an input for these machine learning classification algorithms, the training dataset is transformed into a bag of words where each entry corresponds to the number of occurrences of a particular term in the sentence (Soumya and Pramod, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Semua data yang dihasilkan tersebut kebanyakan berasal dari aplikasi media sosial seperti We Chat, Twitter, Facebook dan Instargram yang memiliki jumlah pengguna yang sangat besar dan tersebar diseluruh dunia. Aplikasi social media telah menjadi bagian dari kehidupan sehari-hari dari orang-orang yang secara terus-menerus berbagi pendapat mereka tentang hidup, informasi, pengetahuan, minat dan sebagainya dalam setiap detiknya [3]. Data dari media sosial menjadi sumber penemuan pengetahuan terbesar dan banyak digunakan bidang analitik big data dengan berbagai metode dan teknik [4].…”
Section: Pendahuluanunclassified
“…The pre-processing stage extracts the semantics, syntax, lengthened, metaphor, etc. Studies have shown that around the world 70% of the internet people use lengthened words for different purposes [22], [23], [24].…”
Section: Introductionmentioning
confidence: 99%